'Hollandse' dorpen in Polen – hoe anders waren ze eigenlijk? - Wenderski, Michał (Werkwinkel. Journal of Low Countries and South African Studies 10(1), 2015)
The ‘Dutch’ colonisation in Poland, which took place between the 16th and the 19th century, left a clear architectural and spatial mark in the Polish countryside. The newcomers, originally from the Low Countries and later from Germany and other parts of Europe, created independent communities which did not establish strong ties with adjacent villages. Moreover, contrary to autochthonic peasants, the colonists enjoyed freedom and a relatively high social status and were often rather wealthy. Hence their villages and farmsteads differed from local ones being generally speaking more representative. It has often been assumed than the ‘Dutch’ settlements in Poland shared more similarities with the Dutch or Frisian countryside than with the neighbouring villages and that both the settlements as well as the farmhouses differed substantially from local building traditions. This paper explores how much the ‘Dutch’ villages and farms were in fact distinguishable from their local counterparts and to what extent they coincided with building traditions in the Low Countries and in Germany.
Keywords: olędrzy; osadnictwo olęderskie